PEMANFAATAN MEDIA DIGITAL SEBAGAI SARANA GREEN CAMPAIGN DI PPS PGOT MARDI UTOMO SEMARANG - Windiani, Reni; Anggraheni, Palupi; Fatharini, Anjani Tri; Pratomo, Muhammad Faiq Adi; Zuliyan, Muhammad Arief; Anjani, Bella Kurnia (Jurnal Pengabdian Vokasi, 2024)
Vast consumerism especially in the fast fashion industry has been criticised by environmentalists since it increased disposable fashion culture. Social media platforms, websites and apps have become key instruments for communities and organisations to spread awareness and drive transformation in the fashion industry. Meanwhile, due to COVID-19 pandemics, many social welfare institutions suffered from decreased funds and affected protection towards people with low income and specified socio-economic conditions at PPS PGOT Mardi Utomo in Semarang. Leveraging digital media for green campaigns can significantly enhance environmental awareness and sustainable practices among the community. By reopening sewing class and increasing added values in upcycling fashion products with simple stitching models. As supply and demand increased, the upcycling fashion activities needed specific strategies  in ensuring sustainable raw  materials from clothing donation. The utilisation of social media increases people's awareness in eco-friendly campaigns. Wider digital campaign coverage can increase public understanding and participation in donating or purchasing products. The growth of donations through momentum such as Green Ramadan and the introduction of digital campaigns can increase the motivation and entrepreneurial skills of the beneficiaries.